An assessment of the interlanguage of Korean adult bilingual students of English in terms of communicative competence - Kim, Nam Gook
This objectives of this study were: to describe the interlanguage of Korean adult bilingual students who are studying in the Philippines in terms of the 4 areas of communicative competence, namely, grammatical, sociolinguistic, discourse, and strategic; to identify the common grammatical error types committed; and to assess the level of intelligibility and acceptability of their utterances as judged by native and non-native speakers of English. The subjects included 15 male Korean subjects studying undergraduate courses in UP and UST.The results of the study showed that in terms of grammatical competence, the subjects were far from adequate. Except for formulaic expressions, they had difficulty in expressing smooth, straight English.